Efficient Dual Cas9 Nickase Correction of a Prevalent Pathogenic LAMB3 Variant for Junctional Epidermolysis Bullosa - Alex du Rand; John Hunt; Daniel Verdon; Ben Buttle; P. Rod Dunbar; Diana Purvis; Vaughan Feisst; Hilary Sheppard (JID Innovations)
Gene editing facilitated by homology-directed repair represents a promising strategy for precisely correcting pathogenic variants underlying monogenic disorders, including the life-threatening skin blistering condition junctional epidermolysis bullosa (JEB). Frequent reports of unintended off-target genotoxicity associated with conventional Cas9 nuclease editing have increasingly led to the adoption of dual-Cas9 nickases (dual-Cas9n) owing to their improved safety profile. However, rates of precise repair obtained with such strategies remain low. In this study, we establish a dual-Cas9n approach targeting LAMB3, using electroporation to deliver Cas9-nickase ribonucleoproteins and modified single-stranded oligodeoxynucleotide repair templates into primary JEB keratinocytes. Targeting a hotspot pathogenic variant (c.1903C>T, p.R635∗), we report perfect correction efficiencies of up to 54% based on standard next-generation sequencing. Using a high-fidelity Cas9 nuclease, we also report perfect repair of up to 74% when using a small-molecule modulator of DNA repair. Dual-Cas9n–corrected JEB keratinocytes demonstrated restored laminin-332 expression and secretion in vitro, leading to improved cellular adhesion and accurate laminin-332 localization in engineered skin equivalents. This protocol represents a significant improvement in precision gene repair using Cas9 nickases for epidermolysis bullosa, with the potential to be applied to a large cohort of patients harboring this prevalent pathogenic variant.